2010
DOI: 10.1111/j.1095-8649.2010.02739.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the maturation transition in haddock Melanogrammus aeglefinus

Abstract: The timing of maturation in haddock Melanogrammus aeglefinus was examined using changes in gonad development, follicle stimulating hormone β (FSH-β) transcript expression profile, growth and condition of 1 year old females held under a common environment between the summer and winter solstices. The circumnuclear ring, cortical alveolus and vitellogenic oocyte stages were first observed in August, October and November, respectively. FSH-β transcript levels did not change significantly until September but increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Such year classes which mature younger and smaller may consequently be smaller at older ages (Taylor & Stefánsson, 1999). Recent experiments carried on North Sea M. aeglefinus revealed that the decision to mature occurs between June and August and is possibly linked to the energy status of the fish (Tobin et al , 2010). Thus, providing that the faster growth of young individuals is associated with a better energy status, this could imply that M. aeglefinus at high temperature would mature in the current year rather than delaying maturity for the next year.…”
Section: Discussionmentioning
confidence: 99%
“…Such year classes which mature younger and smaller may consequently be smaller at older ages (Taylor & Stefánsson, 1999). Recent experiments carried on North Sea M. aeglefinus revealed that the decision to mature occurs between June and August and is possibly linked to the energy status of the fish (Tobin et al , 2010). Thus, providing that the faster growth of young individuals is associated with a better energy status, this could imply that M. aeglefinus at high temperature would mature in the current year rather than delaying maturity for the next year.…”
Section: Discussionmentioning
confidence: 99%
“…At the completion stage, there are several layers of spermagonial cysts, sperm cells and developed testicular ducts with enzyme activity, and spermatozeugmata (sperm bundles) are present (Schreibman et al ., 1982; Koya et al ., 2003). We consider the initiation of maturation to be a good representation of male maturation ‘decision’ in guppies; it is the time when they commit to maturation, reflecting more accurately the factors that affect maturation than the final maturation stage (Tobin et al ., 2010; Harney et al ., 2012; Diaz Pauli and Heino, 2013). Therefore, in the present study we assessed the effect of oxygen and size selection on the initiation of maturation, from now on referred to as maturation.…”
Section: Methodsmentioning
confidence: 99%
“…3, S1, S2) and feature age integration (Table 1). This finding highlights the importance of using traits at the beginning of maturation rather than the end (Tobin et al 2010). Approaches such as measuring changes in hormone titers or patterns of gene expression may allow more accurate estimation of when the maturation process begins.…”
Section: Determinantsmentioning
confidence: 98%
“…Any of these maturation "indicators" can be used to model PMRNs. We would expect those based on IM-1 to most accurately describe the role of age and size in initiating maturation (Davidowitz and Nijhout 2004;Wright 2007;Tobin et al 2010), but those based on IM-3 may be useful in understanding the trade-off between growth and reproduction. PMRNs based on all three maturation indicators were investigated, to describe how effects of age and size changed over the course of the maturation process.…”
Section: Maturation Indicators In Daphniamentioning
confidence: 99%
See 1 more Smart Citation